A Prospective Double-Blind Study of Side Effects Associated with the Administration of Amantadine for Influenza A Virus Prophylaxis - Bryson, Yvonne J.; Monahan, Carolyn; Pollack, Melanie; Shields, W. Donald (The Journal of infectious diseases, 1980)
During a study of efficacy of amantadine prophylaxis of influenza A virus infection in young adults, gross and subtle side effects were monitored. Eighty-eight students were randomly selected to receive either amantadine or placebo for four weeks or both in a sequential crossover design of two weeks each. Side effects (i.e., dizziness, nervousness, and insomnia) occurred in 33% of those receiving amantadine and in 10% of those receiving placebo (P < 0.005). Although side effects were well tolerated by most subjects, six volunteers discontinued amantadine because of marked complaints. Cessation of side effects occurred in more than half of those continuing amantadine. Sixteen students receiving amantadine had decreased performance on sustained attention tasks as compared with ones receiving placebo (P < 0.05). Gross and subtle side effects of amantadine observed in this study on currently recommended dosage are higher than previously reported, which may be an important factor in consideration of mass prophylaxis.